أثر تدريب الخط العربي القائم على نظرية الترميز الثنائي لآلان بايفيو في تنمية مهارتي القراءة و الكتابة لدى طلاب معهد ليمكا القرآني لتحسين و دراسة الخط العربي سوكابومي جاوى الغربية - Iman Syaeful Muminin; Muhamad Jalaludin; Mulyadi Mulyadi (Qawa’id: Jurnal Bahasa dan Sastra Arab, 2026)
This study aimed to investigate the effect of an Arabic calligraphy training program based on Dual Coding Theory on developing reading and writing skills among students in Islamic boarding schools. A quasi-experimental method with a pretest posttest control group design was employed. The sample consisted of 50 students, equally divided into an experimental group and a control group. The experimental group received Arabic Naskh calligraphy training designed according to the principles of Dual Coding Theory, while the control group was taught using conventional instructional methods. Data were collected through reading and writing achievement tests, an observation checklist assessing handwriting accuracy, and a motivation questionnaire toward learning Arabic. The collected data were analyzed using descriptive statistics and an Independent Samples t-test. The findings revealed statistically significant differences in the post-test scores in favor of the experimental group. Furthermore, the experimental group demonstrated a higher level of learning motivation than the control group. These findings indicate that integrating the visual representation of Arabic calligraphy with verbal processing enhances students’ reading and writing performance, strengthens long-term memory retention, and increases learning motivation. The study concludes that Arabic calligraphy can function not only as an artistic practice but also as an effective cognitive and pedagogical strategy for Arabic language instruction. Therefore, integrating calligraphy training into Arabic language curricula is recommended, and further research is encouraged across different educational contexts and language skills.